Exploring entrepreneurial genetic code of smart cities. (9th November 2021) - Crecente, Fernando; Sarabia, María; Carrillo, Francisco; Val, María Teresa Del
Smart cities are key players in the digital economy; their essence is to transformation living, housing and consuming in a sustainable way. The aim of this paper is to explore the entrepreneurial genetic code of smart cities. In this way, smart cities are born to smart entrepreneurships which means that the origin of this smart universe, its genetic code, is smart entrepreneurship. Using a sample of 48 Spanish cities obtained from databases such as the National Statistics Institute (NSI) and the Iberian Balance Analysis System between 2015 and 2019, we analyse the differences between smart habitat. Some demographic, economic and social variables are used for identifying smart universe understood as smart entrepreneurship and city. Logit modelling is used to identify the significant variables to explain smart cities. Some of these variables are ICT entrepreneurship, university level and median age of citizens and represent the core genetic code of smart cities. This paper concludes that smart entrepreneurship has a unique entrepreneurial genetic code which can create differences between smart cities. Entrepreneurship and city are the power couple to develop better smart ecosystems.